Pengaruh TGT Berbantuan Game Kahoot Terhadap Hasil Belajar Matematika Di SDN 20 Kota Bengkulu - Hanura, Farsela; Agusdianita, Neza; Noperman, Feri (JURIDIKDAS, 2025)
This Study aims to insvestigate the impact of the teams games tournament (TGT) learning model, supported by the kahoot game, on the academic perfomance of fifth grade students in mathematics at SDN 20 Bengkulu City. This quantitativeresearch employed a quasy-experimental desing with a matching-only pretest-posttest control group. The population included several elementary schools in a cluster, and cluster random sampling was utilized for participant selection. The experimental group consisted of class VB, while class VC served as the control group. A multiple-choice test sheet was employed as the research instrument, administered before and after the learning sessions in both the experimental and control classes. Data analysis involved descriptive statistical analysis and inferential analysis using the t-test. The results of the t-test, with a t-count value of 1.8585 and a t-table value of 1.7716 at a 5% significance level, indicated statistical significance (t-count>t-table). Therefore, it can be concluded that the Teams Games Tournament (TGT) model, complemented by kahoot game, exerts a statistically significant positive on student learning outcomes in mathematics at SDN 20 Bengkulu City.